The association of non-alcoholic fatty pancreas disease and glycemic status - Singh, Pashaura; Singh, Kamalpreet; Dhanju, Avtar Singh; Singh, Gurinder Bir; Batra, Pranjali; Kaur, Alaipreet (International Journal of Advances in Medicine, 2022)
Background: Non-alcoholic fatty pancreas disease (NAFPD) is an emerging clinical entity. NAFPD is characterised by excessive fat deposition in the pancreas in the absence of alcohol consumption. Recent studies suggest that NAFPD might be associated with beta cell dysfunction, insulin resistance and inflammation which might lead to development of diabetes. NAFPD might be used as an initial indicator of glucometabolic disturbances and identify the patients with prediabetes. Methods: This was a cross sectional study in which the glycemic status of 50 patients with NAFPD with ultrasonographic evidence of increased echogenicity of pancreas was assessed and association between glycemic variability and NAFPD was determined. The patients were also assessed for the ultrasonographic evidence of fatty liver. Results: Pre-diabetes was noted in 32% subjects while diabetes was noted in 20% subjects. Thus, 52% patients with NAFPD had abnormal glycemic status. The 48% subjects i.e., 24 patients had normoglycemia. The presence of fatty liver was statistically significant in normoglycemia and diabetes mellitus with p=0.001 and 0.045 respectively. No statistically significant association was noted between fatty liver and prediabetes with p=0.175. No causal relationship was seen between fatty liver and glycemic variability in patients with NAFPD. Conclusions: NAFPD is associated with impaired glycemic status. It is also seen frequently with fatty liver. Its early detection may help to identify the patients with prediabetes who may benefit from timely introduction of interventions to reduce the rising morbidity and mortality due to diabetes mellitus.